Evolving Concepts of Emotion and Motivation - Berridge, Kent C. (Frontiers in Psychology, 2018)
This review takes a historical perspective on concepts in the psychology of motivation and emotion, and surveys recent developments, debates and applications. Old debates over emotion have recently risen again. For example, are emotions necessarily subjective feelings? Do animals have emotions? I review evidence that emotions exist also as core psychological processes, which have objectively detectable features, and which can occur either with subjective feelings or without them. Evidence is offered also that studies of emotion in animals can give new insights into human emotions. Beyond emotion, motivation concepts also have changed over decades, and debates still continue. Motivation was once thought in terms of aversive drives, and reward was thought of in terms of drive reduction. Motivation-as-drive concepts were largely replaced by motivation-as-incentive concepts, yet aversive drive concepts still occasionally surface in motivation neuroscience today. Among incentive motivation concepts, incentive salience is a core process, mediated by brain mesocorticolimbic systems (dopamine-related systems) and sometimes called ‘wanting’ (in quotation marks), to distinguish it from cognitive forms of desire (wanting without quotation marks). Incentive salience as ‘wanting’ is separable also from pleasure ‘liking’ for the same reward, which has important implications for several human clinical disorders. Ordinarily, incentive salience adds motivational urgency to cognitive desires, but ‘wanting’ and cognitive desires can dissociate in some conditions. Excessive incentive salience can cause addictions, in which excessive ‘wanting’ can diverge from cognitive desires. Conversely, lack of incentive salience may cause motivational forms of anhedonia in depression or schizophrenia, whereas a negatively-valenced form of ‘fearful salience’ may contribute to paranoia. Finally, negative ‘fear’ and ‘disgust’ have both partial overlap but also important neural differences.